MODELLING OF TIME-LAPSE SEISMIC AND GEOMECHANICAL ANALYSIS FOR CO2 SEQUESTRATION MONITORING IN GUNDIH GAS FIELD - Nuwara, Yohanes
Most oil and gas fields around the world releases CO2 from their production to the atmosphere which causes extensive global warming. In Gundih Field, Central Java, Indonesia, for instance, the CO2 emission is as high as 800 tons per day while producing gas from the field. Therefore, the CO2 is proposed to be injected into carbonate reservoir of Kujung Formation in this Field. This proposal is so-called the pilot project of carbon capture, utilization, and storage or CCUS. As means of ensuring that the injection is safe and sustainable for long term, a monitoring activity is required. In this study, a time-lapse 2D seismic survey and geomechanical modeling is proposed for monitoring strategy. The time-lapse seismic survey is expected to detect and locate the CO2 plume with high resolution. To prove the effectiveness of the method, seismic modeling using NORSAR® and seismic data processing using ProMAX are done in this study. This modelling requires subsurface models provided from the available studies in reservoir geology and geophysics, and reservoir simulation as well. Also, the rock acoustic properties both at baseline and post-injection condition are obtained from rock physics modelling. The modelled seismic survey uses 5 km-long seismic line, 251 shots, 501 receivers, 20 m-long shot spacing, and 10-m long receiver spacing with split-spread acquisition geometry. The modelling uses minimum-phase Ricker wavelet with dominant frequency of 50 Hz, where the attenuation is omitted. As the outcome, the CO2 plume can be clearly detected during monitoring program of both after 2 years and 10 years. Next, the poststack acoustic impedance inversion is conducted on the processed seismic data result that exactly shows the geometry of CO2 plume. At the end of this study, a MATLAB® program is created to run a simple modelling of geomechanical response of the reservoir rock to the injected CO2. The increasing volume of CO2 causes pore pressure to build up and decreases the effective stress of the rock. As a result, the CO2 injection with rate of 800 ton per day increases the pore pressure by 1.2 MPa after 10 years, which is still far below the critical pressure, and therefore the injection is proven to be sustainable for 10 years and ahead.